root's ability to retain K⁺ correlates with salt tolerance in wheat - Cuin, Tracey Ann; Betts, Stewart A; Chalmandrier, Rémi; Shabala, Sergey (Journal of experimental botany, 2008)
Most work on wheat breeding for salt tolerance has focused mainly on excluding Na⁺ from uptake and transport to the shoot. However, some recent findings have reported no apparent correlation between leaf Na⁺ content and wheat salt tolerance. Thus, it appears that excluding Na⁺ by itself is not always sufficient to increase plant salt tolerance and other physiological traits should also be considered. In this work, it was investigated whether a root's ability to retain K⁺ may be such a trait, and whether our previous findings for barley can be extrapolated to species following a 'salt exclusion' strategy. NaCl-induced kinetics of K⁺ flux from roots of two bread and two durum wheat genotypes, contrasting in their salt tolerance, were measured under laboratory conditions using non-invasive ion flux measuring (the MIFE) technique. These measurements were compared with whole-plant physiological characteristics and yield responses from plants grown under greenhouse conditions. The results show that K⁺ flux from the root surface of 6-d-old wheat seedlings in response to salt treatment was highly correlated with major plant physiological characteristics and yield of greenhouse-grown plants. This emphasizes the critical role of K⁺ homeostasis in plant salt tolerance and suggests that using NaCl-induced K⁺ flux measurements as a physiological 'marker' for salt tolerance may benefit wheat-breeding programmes.